2015
DOI: 10.1186/s40172-014-0017-x
|View full text |Cite
|
Sign up to set email alerts
|

Locus of control and the labor market

Abstract: This paper reviews the role of locus of control in the labor market. I begin with a discussion of the conceptual origins of locus of control, including its relationship to related concepts such as self-efficacy, motivation, and self-control. The relationship between locus of control and labor market success is then summarized. In doing so, I pay careful attention to what we know about three potential mechanisms -human capital investments, hiring decisions, and optimal incentive contracts -through which locus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 104 publications
(24 reference statements)
2
48
0
1
Order By: Relevance
“…Empirical evidence that documents the benefits of internal locus of control is now becoming well established in the labor market literature (for a review, see Cobb-Clark, 2015). Studies in this area have shown that people who have internal locus of control tend to invest more in human capital accumulation than people with an external locus of control, because the former’s expected return to human capital investment is higher (Coleman and DeLeire, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence that documents the benefits of internal locus of control is now becoming well established in the labor market literature (for a review, see Cobb-Clark, 2015). Studies in this area have shown that people who have internal locus of control tend to invest more in human capital accumulation than people with an external locus of control, because the former’s expected return to human capital investment is higher (Coleman and DeLeire, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Locus of control, which is the other non-cognitive skill measurement in this paper, has also been positively associated with labor market outcomes (Heineck and Anger 2010;Cobb-Clark 2015;Caliendo et al 2015). As an example, Heineck and Anger (2010) find that the external 4 locus of control 3 Self-esteem improves from adolescence to about age 50 to 60 years-old when it peaks.…”
Section: Introductionmentioning
confidence: 70%
“…The study further reveals that an internal locus tends to generate more desirable well-being [32]. Entrepreneurs that have an internal locus of control are found to target attainable, however, challenging goals for themselves, and show persistence at the time of distress, experience minimum job dissatisfaction, and are generally more successful [33,34]. From an entrepreneur's point of view, the locus of control is of two types, internal and external.…”
Section: Entrepreneurial Internal Locus Of Controlmentioning
confidence: 83%